NIST SP 800-34-Based Disaster Recovery Plan Framework for the National Committee for Sharia Economics - Khalil Mojadidi; Abba Suganda Girsang (Politeknik Siber Cerdika Internasional, 2026)
Background: In today’s digital era, information technology (IT) infrastructure is critical to organizational operations, making Disaster Recovery Planning (DRP) essential for business continuity. Institutions managing strategic data assets, such as KNEKS, must address risks from disasters, cyberattacks, and infrastructure failures during PDES development. Objective: This study aims to identify KNEKS’s disaster recovery requirements under current and future PDES conditions and to develop a comprehensive DRP framework based on NIST SP 800-34. Methods: A qualitative case study approach was employed using NIST SP 800-34 Rev. 1 as the primary framework, complemented by FIPS 199, SNI ISO 31000, and NIST SP 800-53. Data were collected through semi-structured interviews with IT managers and system administrators, supported by document analysis. Triangulation and member checking were used to ensure validity. Results: The assessment revealed significant gaps in disaster recovery readiness, particularly in formalized policies, technical redundancy, and impact analysis procedures. Based on these findings, a tailored DRP framework was developed, incorporating activation, recovery, and reconstitution phases while maintaining scalability for future PDES expansion. Conclusion: A comprehensive NIST SP 800-34-based DRP is essential to ensure KNEKS’s operational continuity. The proposed framework offers a structured and scalable approach to disaster recovery and provides a practical model for emerging public-sector, data-intensive institutions.